2013
DOI: 10.2147/copd.s40468
|View full text |Cite
|
Sign up to set email alerts
|

Sweeper’s lung disease: a cross-sectional study of an overlooked illness among sweepers of Pakistan

Abstract: BackgroundSweepers are prone to develop chronic obstructive pulmonary disease even without tobacco smoking.PurposeTo investigate roadside dust as a cause of air flow obstruction among sweepers, and the role of spirometry in its preclinical diagnosis.Material and methodsOne-hundred nonsmoking sweepers (aged 30–60 years) of both sexes sweeping on roads for 8–12 hours a day for the Capital Development Authority of Islamabad, Pakistan were used as study participants (Group A). One-hundred healthy nonsmokers (aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…In the present study, there was no correlation between the work experience and pulmonary functions of the exposed group, which is consistent with the findings of the study by Neghab et al ( 35 ). Conversely, Mariammal et al ( 36 ) and Anwar et al ( 12 ) suggested that the number of years of employment affected the pulmonary parameters. Perhaps the lack of significance observed in the current study may be due to the differences in the factors, including the exposure duration, dust concentration and particle size, previous occupations, and the absence of accurate work experience documentation of Zahedan street cleaners.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the present study, there was no correlation between the work experience and pulmonary functions of the exposed group, which is consistent with the findings of the study by Neghab et al ( 35 ). Conversely, Mariammal et al ( 36 ) and Anwar et al ( 12 ) suggested that the number of years of employment affected the pulmonary parameters. Perhaps the lack of significance observed in the current study may be due to the differences in the factors, including the exposure duration, dust concentration and particle size, previous occupations, and the absence of accurate work experience documentation of Zahedan street cleaners.…”
Section: Discussionmentioning
confidence: 98%
“…The incidence and COPD-related mortality has been higher in women than men in recent years ( 11 ). The long and continuous inhalation of non-industrial dust in Pakistani street sweepers has been reported to be one of the critical factors in the development of COPD, resulting in obstructive ventilatory patterns ( 12 ). When compared with other health hazards, respiratory problems are more prevalent among Indian cleaners ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…The study further revealed that use of personal protective equipment (PPE) was essential in preventing this. Other studies have equally revealed that street sweepers by virtue of their exposure to dust were more likely to have a FEV 1 /FVC ratio less than 60% [16,29]. Office cleaners are also at risk of developing lung function impairment due to exposure to indoor sources of PM 2.5 like chemical detergents and fungal spores from furniture [30].…”
Section: ) Pollutionmentioning
confidence: 99%
“…This shows that street sweepers are more likely to have impaired pulmonary function than office cleaners. Indeed other associated street sweeping and exposures to large amounts of dust with respiratory conditions [22,29].…”
Section: Lung Function Characteristics Of Participantsmentioning
confidence: 99%
See 1 more Smart Citation